1993
DOI: 10.1128/aac.37.10.2144
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of [18F]fleroxacin in healthy human subjects studied by using positron emission tomography

Abstract: Positron emission tomography (PET) with [18Fjfleroxacin was used to study the pharmacokinetics of fleroxacin, a new broad-spectrum fluoroquinolone, in 12 healthy volunteers (9 men and 3 women). The subjects were infused with a standard therapeutic dose of fleroxacin (400 mg) supplemented with -20 mCi of[18F]fleroxacin. Serial PET images were made and blood samples were collected for 8 h, starting at the initiation of the infusion. The subjects were then treated with unlabeled drug for 3 days (400 mg/day). On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…The tissue pharmacokinetics of fleroxacin and trovafloxacin were studied in healthy subjects using positron emission tomography. Both quinolones exhibited a similar pattern of distribution with significant accumulation in all peripheral organs, also in the heart [94,95].…”
Section: In Vivo Antibioticsmentioning
confidence: 75%
“…The tissue pharmacokinetics of fleroxacin and trovafloxacin were studied in healthy subjects using positron emission tomography. Both quinolones exhibited a similar pattern of distribution with significant accumulation in all peripheral organs, also in the heart [94,95].…”
Section: In Vivo Antibioticsmentioning
confidence: 75%
“…The primary focus of SPECT was not the field of anti-infective drug evaluation but cancer research, and it is also used for staging, for diagnostic purposes (such as fever of unknown origin or otitis externa), and for local blood flow measurements (26,182). In vivo SPECT studies enabled quantitative measurements of the tissue PK of 57 Co-or 111 In-labeled bleomycin and 195m Pt-cisplatin in humans (61,77) and indicated that there is marked variability in drug delivery to given tissues. In the field of antibiotic evaluation, SPECT was used to evaluate the penetration of 99m Tc-labeled ciprofloxacin into inflammatory lesions (156).…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 99%
“…As a conceptual extension of autoradiography (7,145,173), several novel imaging methods that lend themselves to the study of drug distribution in humans were developed (26,53,55,56,57,61,64,74,77,83,88,128,147,150,156,158,182,187). These comprised radiopharmaceutical techniques, such as two-dimensional planar gamma scintigraphy (PGS) (88,174), and three-dimensional techniques, such as single photon emission computed tomography (SPECT) (26,61,77,182), positron emission tomography (PET) (56,57,128,188) (Fig. 1), and magnetic resonance spectroscopy (MRS) (83,129,187), which does not require radioactive labeling.…”
Section: Methods For Studies Of Target Site Drug Distribution In Antimentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,18) Fleroxacin reaches peak kidney concentrations within 0.5-1 h. In fact, high concentrations of fleroxacin have been measured in the kidney of rabbits 19) and in the human kidneys. 20) Moreover, the accumulation of fleroxacin was higher in the kidneys of patients with symptomatic complicated urinary tract infections. 21) To our knowledge, there are no data on the effects of fleroxacin (orally) on the nephrotoxicity of administered isepamicin.…”
mentioning
confidence: 99%